Rajan turvallistaminen ja poikkeustilan arjen geopolitiikka: Tornion kaupunki maahantulon reittinä syksyllä 2015 - Prokkola, Eeva-Kaisa (Alue ja Ympäristö, 2018)
In the autumn of 2015 more than 32 000 asylum-seekers arrived in Finland, most of them traveling through the Tornio border crossing point from Haparanda, Sweden. The situation was exceptional and as a response, the Finnish government relocated hundreds of security authorities and servicemen to register the asylumseekers and to control the border crossing. In the research literature such a border securitization, an approach where migrants and asylums are approached from the viewpoint of security instead of human rights, is considered problematic. This paper examines the local authorities and civic actors’ stories of border securitization and asylum reception in Tornio by employing everyday geopolitics as a theoretical and methodological framework. Everyday geopolitics approach is sensitive to the practices and experiences of border securitization at local and intimate scales. The main research finding is that local actors are aware of the wider geopolitical and societal discourses of threat. However, their stories of local and everyday practices emphasize feelings of safety, trust and cooperation at both national and supranational scales. Instead of focusing the feelings of safety merely on the discursive production of threat and danger, it is important to unfold the more contextual, local and mundane interpretations of border securitization.